Association between chest CT features and clinical course of Coronavirus Disease 2019. (July 2020) - Luo, Zhibing; Wang, Na; Liu, Ping; Guo, Qian; Ran, Linyu; Wang, Feilong; Tang, Yuling; Li, Qiang
Abstract: Purpose: This retrospective study aims to illustrate the radiographic characteristics of Coronavirus Disease 2019 and the correlation with the clinical course. Methods: 195 hospitalized patients confirmed as Coronavirus Disease 2019 at First Hospital of Changsha, Hunan Province from December 31, 2019 to February 20, 2020 were enrolled. Chest computed tomography scan, clinical data and laboratory tests results were collected accordingly. Variable characteristics were recorded, radiographic evolution and outcome were analyzed along with the time course. Representative laboratory tests results were analyzed based on the image findings. Results: Majority of the patients showed bilateral (73.8%), multiple lobes involvements (75.9%), peripheral distribution (83.1%), ground-glass opacification (41.0%), increased vascular margins (63.1%), long axis parallelism (55.9%), patchy ground-glass opacities beneath the pleura (51.3%) and consolidation (45.6%). According to the repeated radiology analysis, patients of improving/stable group tended to have younger age compared with worsening group (45.3 ± 15.0 VS. 59.3 ± 13.5, P = 0.001). Based on the laboratory test results, patients with positive image findings shared elder age, 46.0 (35.0–60.0)VS.31.0 (12.0–37.0) P < 0.001, and higher chance developing fever(P < 0.05); higher level of lymphocytes, C-reactive protein, erythrocyte sedimentation rate and lactate dehydrogenase; lower level of white blood cells, neutrophil and albumin(P < 0.001). Conclusions: There are several specific image changes along with the disease progression may be helpful in early recognition and differential diagnosis of Coronavirus Disease 2019. Comprehensive assessments of both imaging feature and laboratory test results may offer an intact knowledge of Coronavirus Disease 2019. Highlights: Certain characteristics were identified of CT scan among COVID-19 patients. Radiographic features changed along with the clinical time course. No predictive value was found of radiographic features on COVID-19 progression. Positive CT findings had correlation with clinical features.